Investigation of SCCmec types I–IV in clinical isolates of methicillin-resistant coagulase-negative staphylococci in Ahvaz, Southwest Iran - Abbasi Montazeri, Effat (Biosci Rep, 2020)
Today methicillin resistant coagulase-negative staphylococci (MR-CoNS) are important in terms of causing significant nosocomial infections. Besides, MR-CoNS are confirmed as the reservoir of SCCmec elements that carry mecA (methicillin-resistant) gene. Hence, the present study was designed to evaluate the susceptibility pattern, prevalence and diversity of SCCmec types I, II, III, and IV in MR-CoNS strains. In this cross-sectional study, 44 clinical isolates of MR-CoNS were identified using the cefoxitin disc method and further confirmation by polymerase chain reaction (PCR) amplification of the mecA gene. Antimicrobial susceptibility of isolates was investigated by disc diffusion. The identification of CoNS was done by amplification and sequencing of the tuf gene. Multiplex PCR method was done for the determination of SCCmec types. In the present study, the Staphylococcus epidermidis and Staphylococcus haemolyticus were the most predominant isolates with a prevalence of 45.4%. The highest resistance rates were observed against erythromycin (84.1%) and clindamycin (75%). Multiplex PCR revealed the SCCmec type I as the predominant type in the present study. Our study showed that there was no significant relationship between the presence of different types of SCCmec elements and resistance to antibiotics. The present study highlighted a frequent prevalence of MR-CoNS harboring SCCmec type genes in Ahvaz, southwest of Iran. Thus, the molecular typing and periodical monitoring of their drug resistance pattern should be considered in national stewardship programs to designing useful antibiotic prescription strategies.